Supernova bounds on the dark photon using its electromagnetic decay - Demos Kazanas; Rabindra N. Mohapatra; Shmuel Nussinov; Vigdor L. Teplitz; Yongchao Zhang (Nuclear Physics B, 2015)
The hypothetical massive dark photon (γ′) which has kinetic mixing with the SM photon can decay electromagnetically to e+e− pairs if its mass m exceeds 2me, and otherwise into three SM photons. These decays yield cosmological and supernovae associated signatures. We briefly discuss these signatures, particularly in connection with the supernova SN1987A, and delineate the extra constraints that arise on the mass and mixing parameter of the dark photon. In particular, we find that for dark photon mass mγ′ in the 5–20 MeV range arguments based on supernova 1987A observations lead to a bound on ϵ which is about 300 times stronger than the presently existing bounds based on energy loss arguments.